Extensor Digitorum Brevis Manus presenting as a symptomatic lump on the dorsum of the hand - Sheetij Kumar Shekhar, MBChB, MRCSEd, DO-HNS, FRCR; Michael Paddock, MSc, MBBS, FRCR; Nikhil Kotnis, MBChB, FRCR (Radiology Case Reports, 2020)
Lumps in the hand are a common presenting complaint in General Practice. We present the case of a 24-year-old male who presented to his General Practitioner with a painful lump in the dorsum of his right hand. He was referred to the sarcoma services where MRI and ultrasound examinations revealed an accessory Extensor Digitorum Brevis Manus muscle as the cause of the patient's symptoms. When patients present with a painful or discomforting lump in the dorsum of the hand during or after repetitive use, typically on flexion, a diagnosis of Extensor Digitorum Brevis Manus should be considered.